Challenges and commonly used countermeasures in the implementation of lifelong antiretroviral therapy for PMTCT in Central Uganda: Health providers' perspective. - Aggrey David Mukose; Hilde Bastiaens; Fredrick Makumbi; Esther Buregyeya; Rose Naigino; Joshua Musinguzi; Jean-Pierre Van Geertruyden; Rhoda K Wanyenze (PLoS ONE, 2023)
Introduction Uganda has implemented lifelong antiretroviral therapy for the prevention of mother-to-child HIV transmission since September 2012. Implementation of this strategy has been met with health provider and client challenges which have persisted up to date. This study explored providers' perspectives on the challenges and countermeasures of the implementation and scale-up of lifelong ART among pregnant and breastfeeding women. Methods A qualitative descriptive study was conducted whereby 54 purposively selected participants from six facilities in three districts of Central Uganda namely; Masaka, Mityana, and Luwero were recruited. A key informant interview guide was used to collect data from the study participants. The data were thematically analysed using Atlas-ti, Version 7. Results Study participants reported challenges under the themes of 1) inadequacy of HIV service delivery (lack of relevant training, health provider shortages, inadequate counselling, stock-outs of essential HIV commodities); 2) Non-utilization of HIV services (Non-disclosure of HIV- positive results, denial of HIV positive results, fear to be followed up, unwillingness to be referred, large catchment area, lack of transport); and 3) Suboptimal treatment adherence (fear of ART side effects, preference for traditional medicines, low male partner involvement in care and treatment). Strategies such as on-job training, mentorship, task shifting, redistribution of HIV commodities across facilities, accompanying of women to mother-baby care points, ongoing counseling of women, peers, and family support groups were commonly used countermeasures. Conclusions This study highlights key challenges that health providers face in implementing lifelong antiretroviral therapy services among pregnant and postpartum women. Context-specific, innovative, and multilevel system interventions are required at national, district, health facility, community and individual levels to scale up and sustain the lifelong antiretroviral therapy strategy among pregnant and breastfeeding women.